2016
DOI: 10.14503/thij-15-5091
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Bilateral Pulmonary Artery Stenoses and Superior Vena Cava Syndrome in a Patient with Advanced Mediastinal Fibrosis

Abstract: 1 In severe cases, it can progress to obstruction of the superior vena cava (SVC), pulmonary vessels, esophagus, or airways. Whereas SVC obstruction is relatively common, pulmonary artery (PA) involvement is less frequently encountered.2 Very few reports of long-term outcomes exist in the medical literature of either SVC or PA stents in this patient population. We discuss a case in which MF resulted in PA and SVC stenoses that were treated endovascularly, with early symptom improvement and 5-year survival with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Catheter angiography was once the modality of choice for evaluation of vascular stenosis and/or compromise due to FM but now has been largely replaced by CT angiography and MR angiography. The current main role of conventional angiography is assessment of the extent of disease before placement of vascular stents and evaluation of stent and/ or vascular patency if CT angiographic and MR angiographic findings are indeterminate (36,37).…”
Section: Imaging Modalities and Features Of Granulomatous And Nongranmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter angiography was once the modality of choice for evaluation of vascular stenosis and/or compromise due to FM but now has been largely replaced by CT angiography and MR angiography. The current main role of conventional angiography is assessment of the extent of disease before placement of vascular stents and evaluation of stent and/ or vascular patency if CT angiographic and MR angiographic findings are indeterminate (36,37).…”
Section: Imaging Modalities and Features Of Granulomatous And Nongranmentioning
confidence: 99%
“…Nonsurgical and surgical procedures are reserved for patients with clinical symptoms directly related to compression and/or obstruction of mediastinal structures. Nonsurgical procedures such as percutaneous transluminal angioplasty with or without stent placement may be used in patients with symptomatic or bilateral vascular obstruction (Figs 19, 20) (36,37,41,43,(69)(70)(71)(72). Studies have shown these procedures to be generally safe and effective when performed by experienced providers and in the appropriate patient population.…”
Section: Prognosis Treatment and Imaging Surveillancementioning
confidence: 99%
“…Brown and colleagues [4] published a report about operative strategies in MF with PA occlusion, in which 5 patients with PA occlusion were described who The limitations for surgical intervention were listed as extensive fibrosis, calcification, and collateral vessels [4]. Stenting may be another option to relieve symptoms of pulmonary hypertension with an extraluminal component only [5]. Although successful PA stenting has been reported in case series, the long-term outcomes are mostly unknown.…”
Section: Commentmentioning
confidence: 99%